Data-driven prediction of antiviral peptides based on periodicities of amino acid properties - Kieslich, Chris A.; Alimirzaei, Fatemeh; Song, Hyeju; Do, Matthew; Hall, Paige (Computer Aided Chemical Engineering, 2021)
With the emergence of new pathogens, e.g., methicillin-resistant Staphylococcus aureus (MRSA), and the recent novel coronavirus pandemic, there has been an ever-increasing need for novel antimicrobial therapeutics. In this work, we have developed support vector machine (SVM) models to predict antiviral peptide sequences. Oscillations in physicochemical properties in protein sequences have been shown to be predictive of protein structure and function, and in the presented we work we have taken advantage of these known periodicities to develop models that predict antiviral peptide sequences. In developing the presented models, we first generated property factors by applying principal component analysis (PCA) to the AAindex dataset of 544 amino acid properties. We next converted peptide sequences into physicochemical vectors using 18 property factors resulting from the PCA. Fourier transforms were applied to the property factor vectors to measure the amplitude of the physicochemical oscillations, which served as the features to train our SVM models. To train and test the developed models we have used a publicly available database of antiviral peptides (http://crdd.osdd.net/servers/avppred/), and we have used cross-validation to train and tune models based on multiple training and testing sets. To further understand the physicochemical properties of antiviral peptides we have also applied a previously developed feature selection algorithm. Future work will be aimed at computationally designing novel antiviral therapeutics based on the developed machine learning models.